Numerical Solution of the Homogeneous Telegraph Equation by Using Galerkin Finite Element Method - Irk, D.; Kirli, E. (Springer, 2020)
In this study, high order numerical solution of one dimensional homogeneous Telegraph equation is presented using quadratic B-spline Galerkin finite element method. In the method, second and fourth order single step methods are used for the time integration. Second order single step method is also known as Crank Nicolson method. The numerical example is studied to illustrate the accuracy and the efficiency of the method. © 2020, Springer Nature Switzerland AG.
4th International Conference on Computational Mathematics and Engineering Sciences, CMES 2019 -- 20 April 2019 through 22 April 2019 -- -- 236359
Keywords: Galerkin Method; Homogeneous Telegraph Equation; Quadratic B-Spline; Galerkin Methods; Interpolation; Numerical Methods; One Dimensional; Splines; Telegraph; Crank-Nicolson Methods; Galerkin Finite Element Methods; Numerical Solution; Quadratic B-Splines; Second Orders; Single-Step Method; Telegraph Equation; Time İntegration; Finite Element Method